Reconciliation, Civil Society, and the Politics of Memory : Transnational Initiatives in the 20th and 21st Century - Schwelling, Birgit (2012)
How did civil society function as a locus for reconciliation initiatives since the beginning of the 20th century? The essays in this volume challenge the conventional understanding of reconciliation as a benign state-driven process. They explore how a range of civil society actors - from Turkish intellectuals apologizing for the Armenian Genocide to religious organizations working towards the improvement of Franco-German relations - have confronted and coped with the past. These studies offer a critical perspective on local and transnational reconciliation acts by questioning the extent to which speech became an alternative to silence, remembrance to forgetting, engagement to oblivion.